Assessment for Islamic Education Learning and Its Impact to Student’s Religiousness of Islamic University - Zurqoni, Zurqoni (IAIN Samarinda, 2018)
Being religious person is absolute for everyone, including the students of Islamic University. That’s why PTKI (Islamic University) does some efforts to strengthen the student’s religiousness. This research is intended to assess the quality of Islamic Education learning and the religiousness of PTKI students and also to observe the implication of this study to student’s religiousness. All students from selected Islamic University in East Kalimantan were taken as the population, and 374 students were chosen as the sample by multistage sampling technique. The technique of dominant data collection was done by doing the survey. The data analysis technique is descriptive analysis and inferential linear regression, through calibration test (validity and reliability), requirement analysis test, normality test, homogenic test, and linearity test. The result of the research has shown that the learning of Islamic Education in Islamic University in East Kalimantan is done well (µ= 4,17). The learning process of Islamic Education in Islamic University has significant influence to student’s religiousness. The learning process of Islamic Education in Islamic University has contributed 54,6% to the increasing of student’s religiousness, while the rest of 45,4% is influenced by other factors. The student’s religiousness in aqeeda aspect is greater than shari’a/muamalah and morals.